Aplikasi dan Diferensiasi Pendidikan Islam - Muhammad Hifdil Islam (Institut Ilmu Keislaman Zainul Hasan Genggong, 2019)
This article explores the use of several Islamic terms, and provides guidance to clarify their use in internal and external discourse. This article describes the typology of Islamic education and the institutions associated with it. It aims to increase understanding of important conceptual differences that depend on subtle language variations such as the differences between Muslim and Muslim education, and between teaching Islam and teaching about Islam. This article then attempts to explain the theoretical conception of “Islamic education,” which considers scripture and the prophetic statement of Islam, along with the commonly held approach to education in Muslim history. This article concludes that the main motivations and characteristics of a holistic and directed education program are divided between Islamic and Western traditions, a phenomenon partly explained by transmission and cumulative divided educational values from classical times to the present.